2016
DOI: 10.1183/16000617.0021-2016
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control in Europe: a policy review

Abstract: Tobacco is responsible for the death of 6 million people every year globally, of whom 700 000 are in Europe. Effective policies for tobacco control exist; however, the status of their implementation varies across the World Health Organization (WHO) European Region. In order to tackle the tobacco epidemic, action has been taken though the implementation of both legally binding and non-legally binding measures. This article aims to present the achievements and challenges of tobacco control in Europe, focussing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…Comprehensive tobacco control policies have been introduced in many European countries during the last 2 decades, especially since the World Health Organization (WHO) Framework Convention on Tobacco Control was signed in 2004 [1,2]. Earlier studies suggested an important impact of these policies on smoking behaviours, both separately [2][3][4][5] and as a comprehensive package [6][7][8][9][10][11]. Furthermore, some policies such as increasing tobacco prices were found to be more effective for low socioeconomic status (SES) individuals [12][13][14], hence potentially reducing socio-economic inequalities in smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive tobacco control policies have been introduced in many European countries during the last 2 decades, especially since the World Health Organization (WHO) Framework Convention on Tobacco Control was signed in 2004 [1,2]. Earlier studies suggested an important impact of these policies on smoking behaviours, both separately [2][3][4][5] and as a comprehensive package [6][7][8][9][10][11]. Furthermore, some policies such as increasing tobacco prices were found to be more effective for low socioeconomic status (SES) individuals [12][13][14], hence potentially reducing socio-economic inequalities in smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The second one, "Health and Politics", is dedicated to more general public health issues (air pollution, European legislation and critique of health systems). The first issue set the pace for the following articles through the contribution of Roberto Bertollini and colleagues from the World Health Organization on European policies against smoking [8].…”
mentioning
confidence: 99%
“…In comparison with other WHO regions, the main difference of smoking prevalence in Europe is that the number of female smokers is much higher making the gap between the prevalence of smoking men and women very small, especially in countries such as Austria, Denmark, Ireland, the Netherlands and the UK [17]. In the latest data of Eurostat, the gender difference of smoking prevalence was estimated in percentage points and showed that countries with higher smoking rates had a bigger gender difference—there was a 24.4% in Lithuania, 15.5 % in Bulgaria and 12.0% in Greece between the prevalence rates of male and female smokers.…”
Section: Discussionmentioning
confidence: 99%